Scaffold Protein SLP-76 Primes PLCγ1 for Activation by ITK-Mediated Phosphorylation. Issue 17 (28th August 2015) - Devkota, Sujan; Joseph, Raji E.; Min, Lie; Bruce Fulton, D.; Andreotti, Amy H.
Abstract: Activation of the phospholipase, PLCγ1, is critical for proper T cell signaling following antigen receptor engagement. In T cells, the Tec family kinase, interleukin-2-induced tyrosine kinase (ITK), phosphorylates PLCγ1 at tyrosine 783 (Y783) leading to activation of phospholipase function and subsequent production of the second messengers inositol 1, 4, 5-trisphosphate and diacylglycerol. In this work, we demonstrate that PLCγ1 can be primed for ITK-mediated phosphorylation on Y783 by a specific region of the adaptor protein, SLP-76. The SLP-76 phosphotyrosine-containing sequence, pY 173 IDR, does not conform to the canonical recognition motif for an SH2 domain yet binds with significant affinity to the C-terminal SH2 domain of PLCγ1 (SH2C). The SLP-76 pY 173 motif competes with the autoinhibited conformation surrounding the SH2C domain of PLCγ1 leading to exposure of the ITK recognition element on the PLCγ1 SH2 domain and release of the target tyrosine, Y783. These data contribute to the evolving model for the molecular events occurring early in the T cell activation process. Graphical abstract: Highlights: Examining the role of SLP-76 pY173 in ITK-mediated activation/phosphorylation of PLCγ1. PLCγ1 adopts an autoinhibited conformation in solution consistent with the reported crystal structure of tandem SH2 domains. The SLP-76 pY173 peptide contains an unusual arginine in the pY + 3 position yet binds to the C-terminal SH2 domain of PLCγ1 disfavoring the autoinhibited form. Binding of SLP-76 pY173 enhances ITK-mediated phosphorylation of PLCγ1 The results add a new function—substrate priming—to the important scaffolding functions of the T cell signaling protein SLP-76.